JENIS TANAMAN INANG DAN MASA INKUBASI PATOGEN BOTRYODIPLODIA THEOBROMAE PAT. PENYEBAB PENYAKIT KULIT DIPLODIA PADA JERUK - Salamiah, Badruzsaufari, dan Muhammad Arsyad . (Universitas Lampung, 2008)
Alternative hosts and Incubation period of Botryodiplodia theobromae the causal of diplodia bark diseases on citrus. Citrus is one of the important horticulture commodities in South Kalimantan. Citrus growers in the region encounter diplodia disease caused by a genus of Botryodiplodia. There is no single method practiced today proved to be effective control for the disease. Insufficient information of the pathogen life cycle is considered to contribute in the failure of disease management. Information of the alternative hosts and incubation period of the pathogens is very crucial in the diseases management. The experiments were carried out at the Laboratory of Plant Diseases and at a Glass House of the Department of Plant Pests and Diseases of the Faculty of Agriculture, Lambung Mangkurat University in Banjarbaru from March – October 2006. The experiments were conducted in three phases, i.e. (1) identification of pathogen, (2) the study of alternative hosts, and (3) the study of incubation periods of the pathogen in the test plants. Results showed that the diplodia disease of citrus “Siam Banjar” was caused by a fungus of the genus Botryodiplodia theobromae. The pathogen can also infected chasew and avocado plants. The Incubation periods of the pathogen in citrus, chasew, and avocado were 64, 39 and 39 days, respectively.